2011
DOI: 10.1371/journal.pone.0023205
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Glucose Transporter 1 (GLUT1) Expression Levels Alters Mouse Mammary Tumor Cell Growth In Vitro and In Vivo

Abstract: Tumor cells exhibit an altered metabolism characterized by elevated aerobic glycolysis and lactate secretion which is supported by an increase in glucose transport and consumption. We hypothesized that reducing or eliminating the expression of the most prominently expressed glucose transporter(s) would decrease the amount of glucose available to breast cancer cells thereby decreasing their metabolic capacity and proliferative potential.Of the 12 GLUT family glucose transporters expressed in mice, GLUT1 was the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
146
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(158 citation statements)
references
References 50 publications
10
146
1
1
Order By: Relevance
“…Therefore, the detection of increased glucose ( 18 F-deoxy-glucose) uptake by positron emission tomography is used for diagnosing tumors and their metastases (Reske et al 1997;Hiyoshi et al 2009). It was reported that GLUT1 expression alters cell growth especially in tumor cells (Young et al 2011). In many cancer cells, for example bladder, brain, breast, lung and more, the expression of GLUT1 seems to be predominant (Medina and Owen 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the detection of increased glucose ( 18 F-deoxy-glucose) uptake by positron emission tomography is used for diagnosing tumors and their metastases (Reske et al 1997;Hiyoshi et al 2009). It was reported that GLUT1 expression alters cell growth especially in tumor cells (Young et al 2011). In many cancer cells, for example bladder, brain, breast, lung and more, the expression of GLUT1 seems to be predominant (Medina and Owen 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, most glycolytic key enzymes are located in the cytosol, which favours immediate ATP supplies for actin rearrangement to facilitate angiogenesis and vesicular secretion and generates required intermediates necessary for cell growth and migration 36, 37. In the present study, we confirmed that down‐regulated HIF‐1α and glycolytic key enzymes expressions in the Hypoxia+HIF‐1α siRNA group could further reduce proliferation and tube formation of hypoxic CMECs compared with Hypoxia group, while QL treatment up‐regulated HIF‐1α and glycolytic key enzymes expressions and promoted proliferation and angiogenesis of hypoxic CMECs.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a study of a panel of 46 breast cancer cell lines revealed their re- markable range of glucose uptake rates and glucose dependences (22). Glucose uptake has been shown to regulate the growth of human breast cancer cell lines via GLUT1 (37), as well as the malignancy of mouse breast cancer cell lines (via GLUT3 amplification) (53).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that the rate of GLUT-dependent glucose uptake can determine mammary epithelial cell growth and the invasive behavior of breast tumor cell lines (37,53,59). Specifically, GLUT1 is the most abundant glucose transporter species in mammary epithelial cells, and knockdown of GLUT1 in mouse mammary tumor cell lines reduces glucose uptake, with a proportional loss of lactate secretion and a corresponding decrease in growth rates, both in tissue culture and in vivo (37). Our study shows that both glucose-limited and Lrp5KD mammary epithelial cells show proportionally less glucose consumption, lactate secretion, and oxygen consumption.…”
Section: Discussionmentioning
confidence: 99%